Isolation and selection of bacteria inhibiting Streptococcus agalactiae causing dark-body disease on snakeskin gourami fish (Trichogaster pectoralis) - Anh Hong, Le Thi; Minh Ngoc, Pham Thi; Khanh, Duong; Tuan, Vo Van; Hoang Dung, Nguyen (Vietnam Journal of Biotechnology, 2021)
Streptococcus agalactiae is one of the microbial pathogens causing the dark-body disease on snakeskin gourami fish (Trichogaster pectoralis) that affects the growth and quality of fish. This research aimed to isolate and select bacteria inhibiting S. agalactiae which are able to use for controling pathogenic bacteria instead of antibiotics. Fourteen bacteria strains were isolated and screened from healthy fishes, sediment and water samples at fish ponds in Dong Thap province. Among these strains, L7 strain showed the highest inhibition ability with the clear zone diameter was 9,3 mm. The results of the 16S rRNA sequence analysis indicated that the L7 strain belonged to Bacillus subtilis. The experiment to evaluate the inhibition capacity and fish disease control of selected B. subtilis in experimental conditions was conducted by challenging fish with S. agalactiae. Fishes in the control treatment was infected with S. agalactiae at 106 CFU/mL had survival rate 41,7%. The experimental treatments NT1, NT2, NT3 which were treated with B. subtilis at concentrations of 105 CFU/mL, 106 CFU/mL, and 107 CFU/mL gave higher survival rates compared with the non-treated control, with the rates of 60%, 76,7%, and 81,7%, respectively. These results revealed that the isolated B. subtilis is potential used in control dark-body disease on snakeskin gourami fish.